Ultrafast two-photon nonlinearities in CdSe near 1.5 mu m studied by interferometric autocorrelation - Schucan, G; Ispasoiu, R; Fox, A; Ryan, J (1998)
We have used interferometric autocorrelation measurements to study the femtosecond nonlinear optical properties of bulk CdSe crystals in the wavelength region just above the half gap wavelength of 1.42 μm. Between 1.42 and 1.55 μm, we measured an ultrafast third-order nonlinearity with nonlinear refractive index n 2 = 1.3 × 10 -13 cm 2/W -1. Detailed modeling of the autocorrelations revealed the influence of higher order effects due to free carriers generated by nonlinear absorption. We find that CdSe is an interesting alternative material to AlGaAs for applications in this technologically important wavelength region.